Does Housing Market impair Job Mobility and Employment in the Czech Republic? - Konečný, Martin (2014)
The main goal of the paper is to find out whether homeownership can have detrimental effect on employment in the Czech Republic. The Oswalds conjecture is tested on the set of panel data across Czech regions between the years of 2005--2012. By testing model similar to the Oswald's I receive the similar result that the rate of homeownership leads to higher rate of unemployment in following years. The second model tested in the paper does not support previous findings that regional rate of homeownership has negative effect on individual's probability of being unemployed. Possible refinements to the model are presented as inspiration for further research.